Helicobacter pylori infection induces duodenitis and superficial duodenal ulcer in Mongolian gerbils. Issue 6 (1st June 2003) - Ohkusa, T; Okayasu, I; Miwa, H; Ohtaka, K; Endo, S; Sato, N
Abstract : Background: There is no direct evidence for an animal model of Helicobacter pylori induced duodenal ulcer. Aim: In this study we evaluated the roles of bacterial strain and age of experimental animals in induction of duodenitis and duodenal ulcer in Mongolian gerbils after H pylori infection. Methods: Specific pathogen free Mongolian gerbils were inoculated orally with three bacterial strains ( H pylori ATCC 43504, TN2GF4, and K-6, a clinical isolate from a patient with gastric cancer in our clinic). These strains have both the cagA gene and VacA. Five week old gerbils were used to emulate prematurity infection and 14 week old animals were used as mature test subjects. Animals were observed for 12 weeks after inoculation. Interleukin 8 (IL-8) production in gastric epithelial cells (MKN74) after coculture with the H pylori strains was measured by ELISA. Results: Gastritis and gastric ulcers were found in all gerbils infected with the three strains. However, duodenitis and gastric metaplasia were seen more frequently in gerbils infected with TN2GF4 and K-6 strains than in the ATCC 43504 infected or control groups (p<0.05). Superficial duodenal ulcers with severe duodenitis and gastric metaplasia were found in two gerbils inoculated at 14 weeks with the TN2GF4 strain but none at five weeks. The TN2GF4 strain stimulated significantly higher levels of IL-8 than ATCC 43504 and K6 strains (p=0.0039). Conclusions: When injected into adult Mongolian gerbils, a specific strain (TN2GF4) of H pylori can induce duodenitis with gastric metaplasia and superficial duodenal ulcers. Induction of duodenal ulcer in an animal model fulfills the requirements of Koch's postulates for establishing a role for H pylori as a causative agent.